Toxic effects induced by vanadium on sea urchin embryos. (July 2021) - Chiarelli, Roberto; Martino, Chiara; Roccheri, Maria Carmela; Cancemi, Patrizia
Abstract: Vanadium, a naturally occurring element widely distributed in soil, water and air, has received considerable interest because its compounds are often used in different applications, from industry to medicine. While the possible medical use of vanadium compounds is promising, its potential harmful effects on living organisms are still unclear. Here, for the first time, we provide a toxicological profile induced by vanadium on Paracentrotus lividus sea urchin embryos, reporting an integrated and comparative analysis of the detected effects reflecting vanadium-toxicity. At the morphological level we found a dose-dependent induction of altered phenotypes and of skeletal malformations. At the molecular levels, vanadium-exposed embryos showed the activation of the cellular stress response, in particular, autophagy and a high degree of cell-selective apoptosis in a dose-dependent manner. The stress response mediated by heat shock proteins seems to counteract the damage induced by low and intermediate concentrations of vanadium while the high cytotoxic concentrations induce more marked cell death mechanisms. Our findings, reporting different mechanisms of toxicity induced by vanadium, contribute to increase the knowledge on the possible threat of vanadium for marine organisms and for both environmental and human health. Highlights: Vanadium exposure caused a dose-dependent response in sea urchin embryos. V exposure correlates with the amount of skeleton produced. V-exposed embryo activated the induction of HSPs, autophagy and apoptosis.